The principle of complementarity : a critical analysis of Article 17 of the Rome Statute from an African perspective - Mohami, Thapelo Adelice (Rhodes University, Faculty of Law, Law, 2014)
This thesis attempts to address perennial concerns, mostly raised in some quarters in Africa, pertaining to the development of the complementarity regime established by the Rome Statute of the International Criminal Court. It grapples with a very important question, whether the principle of complementarity, embodied in article 17 of the Rome Statute, was formulated and is being applied by the ICC in a manner that upholds the ideals and theories upon which the regime was founded. The principle of complementarity is designed to mediate the imperatives of State sovereignty and a legitimate international criminal justice system. Essentially, complementarity gives States latitude to try genocide, crimes against humanity, war crimes and aggression nationally, with the ICC only intervening where States are either unable or unwilling to prosecute genuinely. Africa constitutes the biggest regional block of membership to the Rome Statute, however, over the years; support for the ICC on the African continent has waned. It has been argued in some quarters that the ICC is anti-African and that it has interpreted and applied complementarity in a manner that diminishes State sovereignty. The thesis argues that this tension may also be due to textual deficiencies inherent within the Rome Statute, in the provisions that embody this principle. It therefore examines complementarity from a theoretical perspective to provide a comprehensive account of the system contemplated by the drafters of the Rome Statute. In this regard, the thesis argues for expansion of States' ability at the national level to deal with international crimes without compromising international criminal justice processes or threatening State sovereignty. This is suggested as a way of relieving the tension that has characterised the relationship between African States and the ICC. The thesis further sketches out some of the complexities inherent in the modalities through which the Court may exercise its complementary jurisdiction, particularly within the African continent, given that legal systems in most African countries are particularly weak. It thus dissects the provisions that outline the principle of complementarity in tandem with the Court's interpretation and application of complementarity in practice. Furthermore, through an exploratory survey of the referral of the Situation in Uganda, and the ICC Prosecutor's proprio motu investigation of the Situation in Kenya, the thesis illustrates how a positive approach to complementarity can help establish a healthy cooperative synergy between the ICC and States, thereby promoting a functional expeditious criminal justice system. This will go a long way towards assuaging State's fears that the ICC merely pays lip service to complementarity and arbitrarily supersedes national jurisdiction.
Keywords: Complementarity (International law); Rome Statute of the International Criminal Court (1998 July 17); International Criminal Court; Criminal jurisdiction -- Africa; International crimes -- Africa; Crimes against humanity -- Africa